Can mental health treatments help prevent or reduce intimate partner violence in low- and middle-income countries? A systematic review - W. A. Tol; S. M. Murray; C. Lund; P. Bolton; L. K. Murray; T. Davies; J. Haushofer; K. Orkin; M. Witte; L. Salama; V. Patel; G. Thornicroft; et al. (BMC, 2019)
Abstract Background Epidemiological research suggests an interrelationship between mental health problems and the (re)occurrence of intimate partner violence (IPV). However, little is known about the impact of mental health treatments on IPV victimization or perpetration, especially in low- and middle-income countries (LMIC). Methods We conducted a systematic review to identify prospective, controlled studies of mental health treatments in LMIC. We defined 'mental health treatment' as an intervention for individuals experiencing mental ill health (including substance misuse) including a substantial psychosocial or pharmacological component. Studies had to measure a mental health and IPV outcome. We searched across multi-disciplinary databases using a structured search strategy. Screening of title/abstracts and full-text eligibility assessments were conducted by two researchers independently, data were extracted using a piloted spreadsheet, and a narrative synthesis was generated. Results We identified seven studies reported in 11 papers conducted in five middle-income countries. With the exception of blinding, studies overall showed acceptable levels of risk of bias. Four of the seven studies focused on dedicated mental health treatments in various populations, including: common mental disorders in earthquake survivors; depression in primary care; alcohol misuse in men; and alcohol misuse in female adult sex workers. The dedicated mental health treatments targeting depression or alcohol misuse consistently reduced levels of these outcomes. The two studies targeting depression also reduced short-term IPV, but no IPV benefits were identified in the two alcohol-focused studies. The other three studies evaluated integrated interventions, in which a focus on substance misuse was part of efforts to reduce HIV/AIDS and violence against particularly vulnerable women. In contrast to the dedicated mental health interventions, the integrated interventions did not consistently reduce mental ill health or alcohol misuse compared to control conditions. Conclusions Too few studies have been conducted to judge whether mental health treatments may provide a beneficial strategy to prevent or reduce IPV in LMIC. Key future research questions include: whether promising initial evidence on the effects of depression interventions on reducing IPV hold more broadly, the required intensity of mental health components in integrated interventions, and the identification of mechanisms of IPV that are amenable to mental health intervention.